P137 Practise and Effects of Autoimmune Screening in Pulmonary Fibrosis. (19th November 2012) - Anning, L; Gibbons, MA
Abstract : Introduction and Objectives: Patients with pulmonary fibrosis can have features of autoimmune disorders that do not meet criteria for connective tissue disease (CTD), sometimes referred to as autoimmune-featured interstitial lung disease (AIF-ILD). Incorrect diagnosis and labelling could have important implications for treatment and prognosis. We analysed the prevalence and type of immune profile performed to investigate patients with pulmonary fibrosis to determine what effect it had on subsequent management, and to assess variations in clinical practise. Methods: Retrospective review of patients attending the ILD and general respiratory clinics at our centre (n=75) with a diagnosis of pulmonary fibrosis, not known to be due to a CTD, or to be caused by a drug reaction, hypersensitivity, or sarcoidosis. Results: Seventy-five cases were reviewed (76% male). Age range was 55–88 years (median 73 years). Eighty percent of patients (n=60) had immune tests performed, with 13% (n=10) having two tests, 5% (n=4) having three, and 61% (n=46) having four or more. Twenty-eight percent (n=21) had a positive immune test. A positive immune screen partly directed the introduction of anti-inflammatory therapy in 24% of patients (n=5). One of these patients had a lung biopsy. In 38% of patients with a positive immune screen (n=7) it was unclear if the result contributed to clinical decision making. Lung biopsies were performed in 19% of patients with a positive immune screen, whereas only 8% of the total had a lung biopsy. Conclusions: These results show there is considerable variability in immune screen testing: which tests are performed, how positive tests are interpreted and whether they affect management. Our data hint at the usefulness of immune profiling, particularly where a lung biopsy has not been undertaken, and suggest that an abnormal immune profile increases the rate of lung biopsy. We suggest that a multi-centre, prospective, longitudinal study is required to further define AIF-ILD in terms of incidence, natural history, response to therapy and outcome. Whether AIF-ILD and the other idiopathic interstitial pneumonias are truly distinct remains to be determined, but clearly there is a need for advanced definitions, diagnostic algorithms, and management strategies.